2020
DOI: 10.1016/j.joule.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Cost Overrun in Nuclear Power Plant Construction Call for a New Approach to Engineering Design

Abstract: Nuclear plant costs in the U.S. have repeatedly exceeded projections. Here we use data covering five decades and bottom-up cost modeling to identify the mechanisms behind this divergence. We observe that nth-of-a-kind plants have been more, not less expensive than first-of-a-kind plants. Soft factors external to standardized reactor hardware, such as on-site labor supervision, contributed over half of the rapid cost rise from 1976-1987. Relatedly, reactor containment building costs more than doubled from 1976-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 55 publications
(97 reference statements)
0
37
0
Order By: Relevance
“…Note that these cost components can comprise both physical ''hardware'' costs, such as materials, and also non-hardware ''soft'' costs, such as labor, engineering design, and administration. 48,62 As such, these components can reflect changes in cell materials and designs as well as manufacturing processes, equipment, and overhead. Also note that in this analysis ''input prices'' refer to the prices a technology manufacturer pays to purchase materials that they use in their manufacturing process.…”
Section: Cost Decomposition Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Note that these cost components can comprise both physical ''hardware'' costs, such as materials, and also non-hardware ''soft'' costs, such as labor, engineering design, and administration. 48,62 As such, these components can reflect changes in cell materials and designs as well as manufacturing processes, equipment, and overhead. Also note that in this analysis ''input prices'' refer to the prices a technology manufacturer pays to purchase materials that they use in their manufacturing process.…”
Section: Cost Decomposition Strategymentioning
confidence: 99%
“…44 Recently, a new conceptual framework and dynamic, detailed quantitative models have been applied to study the cost changes observed for notable energy technologies. 35,48 These models start from a cost equation that computes a technology's overall cost scaled by its service (e.g. typically USD W À1 for power generating technologies, USD W À1 h À1 for energy storage technologies, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…When we look at the historical record, the evidence suggests that at the fleet level nuclear power could even have what has been termed a negative rate of learning. In the United States and France, the two countries with the largest nuclear reactor fleets, reactors that were constructed later actually cost more than those constructed earlier [65]- [71]. If this pattern holds for SMRs, it would mean that a small reactor will never catch up on cost with a large reactor of similar design.…”
Section: Can Learning Compensate?mentioning
confidence: 99%
“…The capital cost of nuclear power plants in western countries has significantly increased for multiple reasons. 5,6 One cause is that nuclear plant requirements have evolved over the last 50 years. The original nuclear plant designs followed those of coal plants, i.e., tight integration of the heat source with the turbine generators.…”
Section: High Capital Costsmentioning
confidence: 99%